Maximum Likelihood Joint Tracking and Association in Strong Clutter. (14th January 2013) - Perlovsky, Leonid I.; Deming, Ross W.
We have developed a maximum likelihood formulation for a joint detection, tracking and association problem. An efficient non-combinatorial algorithm for this problem is developed in case of strong clutter for radar data. By using an iterative procedure of the dynamic logic process "from vague-to-crisp" explained in the paper, the new tracker overcomes the combinatorial complexity of tracking in highly-cluttered scenarios and results in an orders-of-magnitude improvement in signal-to-clutter ratio.